If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
-g = (2/3)*x-17 // - (2/3)*x-17
17-g-((2/3)*x) = 0
(-2/3)*x-g+17 = 0
17-g-2/3*x = 0 // - 17-g
-2/3*x = -(17-g) // : -2/3
x = (-(17-g))/(-2/3)
x = -3/2*(g-17)
x = -3/2*(g-17)
| -2x+34=2 | | 4X+35+X+20=180 | | -423=8(3+7p)+1 | | 9/10-4/5p=5/6 | | 6x-30-40=20 | | 3(w-2)=-8 | | 3*r-(1-1)=r+(24/3) | | -2(-1+n)=18 | | ((27p^6)^5/3) | | 15.8x+.5x-130.4=16.3 | | (2x+5)+(x+10)=0 | | 1/9g=-15 | | 3/2x+x/5=17 | | 4.1/5=3p | | 9x+3x=70 | | 225*67/75*1/9 | | (27p^6)^5/3 | | 2079=2x+2(2x-5)+5x+10 | | 3(1-a)=-a+5 | | -98=-28x+2x^2 | | 5(7+n)=37+7n | | 27t+1t=-8t | | 7z-4=13+z | | (a+2)(a-4)+10=(-a-2)(6-a) | | -9-x=-4 | | -5/20c=20 | | 5/5-5/11 | | w/w-3-2w/2w-3=w-5/2w^2-9w+9 | | (4+2x+3x^2+6x^3)-(-4+2x-3x^2+6x^3)= | | 10X+6=9X-5 | | 5-(-9)=-4 | | 7a+10=a |